ASPEK HUKUM PEMBERHENTIAN PEGAWAU NEGERI SIPIL BERDASARKAN PERATURAN PEMERINTAH NOMOR 30 TAHUN 2019 TENTANG PENILAIAN KINERJA PEGAWAI NEGERI SIPIL - Iwan Permadi (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2021)
Performance appraisal of civil servants as stipulated in article 77 number (6) of Law Number 5 of 2014 concerning State Civil Apparatus, this article states that a civil servant whose performance evaluation is not in accordance with the established targets is subject to sanctions in the form of administrative sanctions until dismissal. Basically, the performance of civil servants is the result and assessment of work carried out by civil servants in quality and quantity that has been achieved by a civil servant in carrying out the duties, authorities, obligations and responsibilities that have been given. This changes the paradigm that has been formed so far that being a civil servant is impossible to be dismissed, and a civil servant is not an office employee who is assessed based on performance appraisal, from that background we formulate the issue What is the legis ratio of dismissal of civil servants based on performance appraisal in PP Number 30 of 2019 concerning work evaluation? and What are the legal implications of the dismissal of civil servants based on performance appraisal in PP Number 30 of 2019 concerning Performance Appraisal.